2008
DOI: 10.1017/s003118200800485x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmaand reaction time: role of toxoplasmosis in the origin, preservation and geographical distribution of Rh blood group polymorphism

Abstract: The RhD protein which is the RHD gene product and a major component of the Rh blood group system carries the strongest blood group immunogen, the D-antigen. This antigen is absent in a significant minority of the human population (RhD-negatives) due to RHD deletion or alternation. The origin and persistence of this RhD polymorphism is an old evolutionary enigma. Before the advent of modern medicine, the carriers of the rarer allele (e.g. RhD-negative women in the population of RhD-positives or RhD-positive men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
124
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 37 publications
9
124
3
2
Order By: Relevance
“…It must be remembered that our population of Rh-positive women represents a mixture of homozygotes and heterozygotes. At the same time, current data suggests that protective effects of Rh factor positivity are fully expressed only in the Rh-positive heterozygotes (Novotná et al, 2008;Flegr, 2016). Therefore, future studies should be performed on DNA genotyped populations.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It must be remembered that our population of Rh-positive women represents a mixture of homozygotes and heterozygotes. At the same time, current data suggests that protective effects of Rh factor positivity are fully expressed only in the Rh-positive heterozygotes (Novotná et al, 2008;Flegr, 2016). Therefore, future studies should be performed on DNA genotyped populations.…”
Section: Discussionmentioning
confidence: 90%
“…The case control study performed on 500 blood donors showed that Toxoplasma-infected Rh-positive heterozygotes showed better psychomotor performancenamely, shorter reaction times-than Toxoplasma-free Rh-positive heterozygotes. At the same time, psychomotor performance of infected Rh-positive homozygotes and especially of infected Rh-negative homozygotes was much poorer than that of corresponding controls (Novotná et al, 2008). It has been shown that toxoplasmosis has various effects on human physiology and some of these effects, such as increase of testosterone (Flegr et al, 2008a,b) or partial immunosuppression (Flegr and StříŽ, 2011), could have a positive impact on human performance and health in certain situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the mechanism of the effect of latent toxoplasmosis on human behaviour is unknown; however, we have some indices of deteriorated physical functioning in T. gondiiinfected subjects. these include prolonged simple reaction times (Havlíček et al 2001, Novotná et al 2008, and higher risk of traffic accidents (Flegr et al 2009, Kocazeybek et al 2009) in infected subjects. Deteriorated physical functioning of T. gondii-infected subjects possibly leading to shorter life expectancy could also explain the unexpected phenomenon of decreased seropositivity in the highest age groups in many prevalence studies (e.g.…”
mentioning
confidence: 99%